Exposure to Mycotoxin-Mixtures via Breast Milk: An Ultra-Sensitive LC-MS/MS Biomonitoring Approach - Braun, Dominik; Ezekiel, Chibundu N.; Marko, Doris; Warth, Benedikt (Frontiers in Chemistry, 2020)
Exposure to natural food contaminants during infancy may influence health consequences later in life. Hence, breast milk may serve as a vehicle to transport these contaminants, including mycotoxins, from mothers to their infants. Analytical methods mostly focused on single exposures in the past, thus neglecting co-occurrences and mixture effects. Here, we present a highly sensitive multi-biomarker approach by a sophisticated combination of steps during sample preparation including QuEChERS extraction followed by SPE cleanup and utilizing stable isotopes for compensating challenging matrix effects. The assay was validated in-house, reaching limits of detection (LOD) for all 34 analytes in the range of 0.1 to 300 ng/L with satisfying extraction efficiencies (75 - 109%) and stable intermediate precisions (1 - 18%) for most analytes. Compared to our first published multi-mycotoxin method LODs were decreased by a factor of 2-60x enabling the assessment of chronic low-dose exposures. The new method was applied to a small set of Nigerian breast milk samples to compare results with already published data. Concentration levels of samples determined to be contaminated before could be confirmed. The newly investigated alternariol monomethyl ether (AME) was found for the first time in this biological fluid at concentrations up to 25 ng/L. Moreover, in a pooled Austrian sample trace amounts of multiple mycotoxins confirmed co-occurrence and exposure even in countries with high food safety standards. In conclusion, the method facilitates the determination of mycotoxins at ultra-trace levels in breast milk, enabling the generation of occurrence data necessary for comprehensive co-exposure assessment.